In Situ Reconstructed Layered Double Hydroxides via MOF Engineering and Ru Doping for Decoupled Acidic Water Oxidation Enhancement - Vijayakumar P.; Lenus S.; Pradeeswari K.; Kumar M.; Chang J.-H.; Kandasamy M.; Krishnamachari M.; Dai Z.; Al-Kahtani A.A.; Sankar Krishnan P. (American Chemical Society, 2025)
Discovering cost-effective, durable, and economical electrocatalysts for the lattice oxygen- mediated mechanism (LOM)-based oxygen evolution reaction (OER) under acidic conditions is essential for advancing the commercialization of electrochemical water-splitting devices. In this study, we effectively constructed a distinctive petal-like nanoflake (NFls) structure by introducing ruthenium (Ru) into a NiM (M = Fe, Co) metal-organic framework (MOF) on a nickel foam (NFo) substrate through a straightforward in situ conversion process of layered double hydroxides (LDHs). Utilizing the unique electrochemical properties of this material, the Ru-doped NiFe-BDC/NFo exhibited an impressively low overpotential of ?247 mV at a current density of 10 mA cm-2 when operating in an acidic environment for OER. Most notably, our champion catalysts displayed exceptional long-term stability during continuous operation for 20 h in 0.5 M H2SO4, positioning them as some of the top electrocatalysts for acidic conditions. The exceptional catalytic performance of NiM (M = Fe, Co)-BDC/NFo can be ascribed to the introduction of Ru and the conversion of LDH into a MOF. This transformation significantly enhances reaction kinetics and facilitates charge transfer, ultimately resulting in the attainment of optimal activity for the OER. This research introduces a novel category of electrocatalysts for the OER under acidic conditions, which has been relatively underexplored. ? 2024 American Chemical Society.